Wither Sanctuary? - Lippert, Randy (Refuge: Canada’s Journal on Refugees, 2010)
<!–StartFragment–> Features of all fifty sanctuary incidents occurring in Canada from 1983 to early 2009 are described and recent trends identified. The duration of sanctuary incidents has increased dramatically, the success rate has declined, and no new incidents have commenced in more than one and a half years. Sanctuary’s apparent decline in its “exposure” form as an effective resistance strategy is likely related to several factors, including less interest among mass media, the federal government’s adoption of a more authoritarian approach toward immigration and refugee policy, and the rise of support for a merit-based legal appeal for failed refugee claimants evident in sanctuary discourse. <!–EndFragment–>